2014
DOI: 10.1021/jo5011894
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Molecularly Complex Azaborines: Palladium-Catalyzed Suzuki–Miyaura Cross-Couplings of Brominated 2,1-Borazaronaphthalenes and Potassium Organotrifluoroborates

Abstract: Despite their potential applications in both medicinal chemistry and materials science, there have been limited reports on the functionalization of 2,1-borazaronaphthalenes since their discovery in 1959. To access new chemical space and build molecular complexity, the Suzuki–Miyaura cross-coupling of brominated 2,1-borazaronaphthalenes has been investigated. The palladium-catalyzed cross-coupling proceeds with an array of potassium (hetero)aryltrifluoroborates in high yield with low catalyst loadings under mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 46 publications
1
56
0
1
Order By: Relevance
“…Traditionally, aryl halides are most widely used electrophilic reagents in Pd‐catalyzed Suzuki‐type cross‐coupling reactions with organotrifluoroborates (Scheme , C–X bond) . Subsequently, the methods utilizing aryl ester which derived from the respective phenols in Suzuki‐type coupling with organotrifluoroborates have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, aryl halides are most widely used electrophilic reagents in Pd‐catalyzed Suzuki‐type cross‐coupling reactions with organotrifluoroborates (Scheme , C–X bond) . Subsequently, the methods utilizing aryl ester which derived from the respective phenols in Suzuki‐type coupling with organotrifluoroborates have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…2 These studies demonstrated the stability of these azaborines 3 to transition metal catalysis and allowed access to functionalized molecules that could have applications in medicinal chemistry 4 and/or materials science. 5 During the course of this latter study, we first developed conditions for the cross-coupling of N -H and N -alkyl 3-bromo- B - alkyl -2,1-borazaronaphthalenes (eq 1).…”
Section: Introductionmentioning
confidence: 97%
“…Traditionally, aryl halides are most widely used electrophilic reagents in Pd-catalyzed Suzuki cross-coupling reactions with organotrifluoroborates (Scheme 1, C-X cleavage). [16][17][18][19][20][21][22][23] Subsequently, the methods utilizing aryl tosylates which derived from the respective phenols in Suzuki coupling with organotrifluoroborates have been developed. The transformation proceeded via C-O bond cleavage instead of C-X bond (Scheme 1, C-O cleavage).…”
Section: Introductionmentioning
confidence: 99%